HUBUNGAN EFIKASI DIRI DAN SELF REGULATION TERHADAP KECEMASAN AKADEMIK PADA REMAJA DI SMA NEGERI 3 LANGGAM - Rajagukguk, Sartika; Sari, Sabtria Winda; Ramadhani, Dyah Wulan; Bratha, Shinta Dewi Kasih; Abidda, Lutfa Khoilil (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Academic anxiety arises when there is a mismatch between academic pressures and demands which are considered a burden so that they feel uncertain and not by the abilities that students have. This is what underlies students ' high efficacy in overcoming this anxiety. The purpose of this study is to determine the relationship between self-efficacy and self-regulation in academics in adolescents at senior high schools 3 Langham. The research design used in this study is a quantitative descriptive correlation with a cross-sectional approach. The sampling technique used was purposive sampling of 56 respondents. The research location will be carried out at SMA Negeri 3 Langgam, Segati Village, Langgam sub-district, Pelalawan Regency, Riau. Data collection tools are questionnaire sheets of self-efficacy, self-regulation, and academic anxiety which are analyzed univariately and bivariate with the Fisher Exact test. The results of this study showed that there is a relationship between self-efficacy and self-regulation of academic anxiety in adolescents at SMAN 3 Langgam. It is expected to develop self-efficacy and self-regulation of their abilities by continuing to strive when studying and not giving up easily when doing tasks, especially tasks with high difficulty.Keywords cutaneus: Parenting, Social Support, and Relaps